2005
DOI: 10.1086/427560
|View full text |Cite
|
Sign up to set email alerts
|

Helminthic Infection Down‐Regulates Type 1 Immune Responses in Human T Cell Lymphotropic Virus Type 1 (HTLV‐1) Carriers and Is More Prevalent in HTLV‐1 Carriers than in Patients with HTLV‐1–Associated Myelopathy/Tropical Spastic Paraparesis

Abstract: Human T cell lymphotropic virus type 1 (HTLV-1) infection is associated with an exacerbated type 1 immune response and secretion of high levels of proinflammatory cytokines. In contrast, helminthic infection induces a type 2 immune response. In the present study, the cytokine profile in HTLV-1 carriers coinfected with helminths (Strongyloides stercoralis and/or Schistosoma mansoni) was compared with that in HTLV-1 carriers not coinfected with helminths. Levels of interferon (IFN)- gamma were higher in HTLV-1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 31 publications
0
36
0
3
Order By: Relevance
“…As HTLV-1 is able to induce an exacerbated immune response and this is the basis of the pathology [8], strategies capable of reducing the Th1-inflammatory response are desirable. A previous study conducted by the Immunology Service of the Federal University of Bahia showed that in HTLV-1-infected individuals coinfected with S. mansoni , the levels of IFN-γ in the supernantants of nonstimulated PBMC cultures were higher when compared to HTLV-1 non-coinfected individuals [16]. …”
Section: Discussionmentioning
confidence: 99%
“…As HTLV-1 is able to induce an exacerbated immune response and this is the basis of the pathology [8], strategies capable of reducing the Th1-inflammatory response are desirable. A previous study conducted by the Immunology Service of the Federal University of Bahia showed that in HTLV-1-infected individuals coinfected with S. mansoni , the levels of IFN-γ in the supernantants of nonstimulated PBMC cultures were higher when compared to HTLV-1 non-coinfected individuals [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that S. stercoralis infection promotes development of ATL in HTLV-1 infected individuals [8,9,10], but this hypothesis has been disputed on the grounds that ATL patients infected with Strongyloides have improved responses to chemotherapy [11], and HTVL-1 carriers coinfected with Strongyloides have a lower proviral loads than those with HTVL-1 alone [12]. …”
Section: Discussionmentioning
confidence: 99%
“…The synergistic severity of disease caused by these infections has been suggested to be due to immunocompromise resulting from HTLV-1 as a result of interferon g expression, and shift from Th2 to Th1 responses, resulting in decreased levels of IL4, IL5, IL13, and IgE [4,[16][17][18][19]. Alternatively, a Strongyloides antigen has been postulated to induce a potent polyclonal T-cell mitogenic response, and reactivation of HTLV-1 expression [1,20].…”
Section: Discussionmentioning
confidence: 99%